ASSESSMENT OF THE POSSIBILITY OF ENHANCING INNOVATION AND ITS IMPACT ON THE PROSPECTS OF ENGINEERING ENTERPRISES DEVELOPMENT - A. V. Cherep; Z. I. Simanaviciene; O. H. Cherep; P. V. Hudz (Фінансово-кредитна діяльність: проблеми теорії та практики)
The indicators of industrial enterprises’ attractiveness for innovation are calculated, the profitabilityratio and asset management are assessedof enterprises PJSC «Zaporizhzhia Electric Locomotive Repair Plant», PJSC «MGT PLANT», PJSC «Zaporizhzhia Tool Plant named after Voikov», PJSC Zaporozhtransformator, Motor Sich JSC, PJSC «Zaporizhzhia Mechanical Plant». The indices of profitability, financial soundness, solvency andasset management of engineering enterprises were analysed. The necessity of shaping an innovation activity strategy to improve all activity lines of engineering enterprises was grounded. The interdependence between the indices of profitability, financial soundness, solvency, asset management and innovative attractiveness of engineering enterprises was established. The possibility and necessity of making informed managerial and strategic decisions were proved in order to overcome the non-productive state given the indicators of innovative attractiveness of engineering enterprises. In the context of modern economy, the factors of external and internal environmentaffect the results of engineering enterprises’ activities. Given the availability of information, its timely processing and analysis, not only will they be able to minimize the impact of risks but also analyse the main problems of economic activity and thelevel of innovation development in order to make appropriate decisions. It is established that attractiveness for innovation provides receipt of financial resources that will allow productionmodernization and, consequently, ensuring competitiveness of enterprises not only in the Zaporizhzhia region but also in Ukraine entirely. The impact of profitability, solvency and enterprises’ attractiveness for innovation is revealed. The measureswere suggested with regard to increasingattractivenessfor innovation of engineering enterprises in the Zaporizhzhia region on the basis of formation of the strategy for their development and giventhe management of profitabilityindicators, solvency ratios and efficiencyindicesof enterprises' assetsutilization.